PELAKSANAAN SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PENDIDIKAN AGAMA ISLAM - Nusirwan (UNISAN JURNAL, 2024)
The point of this exploration is to find out. The kind of exploration utilized is enlightening subjective examination, in particular an exploration method that produces clear information as composed or expressed words from individuals and entertainers noticed, coordinated from the singular's experience overall (all encompassing) without disengaging the individual and the association inside. variable yet check it out. as a feature of an entirety. In information assortment procedures in this examination, different methods were utilized, in particular meetings, perception and documentation. The information examination system utilized in this exploration is subjective investigation. The consequences of the examination on Head Oversight Arranging were done in an arranged, methodical and ceaseless way. During the execution of oversight, the central's demeanor obviously didn't obstruct the growing experience of Islamic strict schooling in the homeroom, even toward the finish of the example the chief gave inspiration to understudies to tenaciously review. Islamic Strict Training Educators have great execution in the educational experience. This should be visible from the most common way of planning learning plans which are ready as per the models set out in educator execution principles. At the learning execution stage, the instructor can dominate the class, ace the material well, then the educator can fluctuate showing strategies and use learning media and give open doors to understudies to collaborate with questions and replies. The issue in executing oversight of Islamic Strict Training educators in schools is the low inspiration of educators to complete management..